Pengaruh Usaha Budidaya Bebek Petelur Terhadap Perekonomian Keluarga di Desa Sukamerindu Kecamatan Pemulutan Barat - Anita, Anita; Andriani, Dian Sri; Shomedran, Shomedran (Universitas Mataram, 2024)
This research aims to find out the influence of petal duck business on the family economy in Sukamerindu Village, Indralaya district of Ogan Ilir. The approach used in this research is quantitative with the type of descriptive research. The population of this research is an entrepreneurial duck with a sample of 30 entrepreneurs using a census sample technique. Data collection techniques using observation and lifting. Data analysis techniques using simple linear regression formulas. The results of the research showed that there was an influence between the business of the duck on the family's economy. For influence business ducks belong to the low category. With the result of a ritung value > rtable that is a positive influence on the economy of the family that has a contribution of 0.153 or. That means every 1% increase in the rate of breeding of the duck (X), then the increase in income (Y) will increase by 0.153. As far as the positive impact of the breeding of the duck is concerned, it can be seen from the result that the majority of the community that has an undertaking of breeding ducks is able to meet the daily needs of quality food, have sufficient water, and are able to satisfy daily needs. It can be concluded that the results of the research there is a positive relationship between the cultivation of ducks petal against the economy of the family in the village of Sukamerindu district of Ogan Ilir.